The feeding of rams on farms of the "Macedonia" Cooperative of Chios sheep breeders - VALERGAKIS (Γ. Ε. ΒΑΛΕΡΓΑΚΗΣ) G. E.; GELASAKIS (Α. Ι. ΓΕΛΑΣΑΚΗΣ) A. I.; OIKONOMOU (Γ. ΟΙΚΟΝΟΜΟΥ) G.; BAZDAGIANNI (Ζ. ΜΠΑΣΔΑΠΑΝΝΗ) Z.; ARSENOS (Γ. ΑΡΣΕΝΟΣ) G. (Journal of the Hellenic Veterinary Medical Society, 2017)
The aim of this study was to verify the adequacy of ram rations in intensively reared flocks of the Chios breed. Data were collected from the 66 farms of the "Macedonia" Cooperative of Chios Sheep Breeders and were evaluated using requirements published by INRA and NRC. Statistical analysis was performed using analysis of variance. Ram requirements for net energy lactation, digestible protein, absorbable calcium and absorbable phosphorus were greatly exceeded. Farm classification in three groups (A, Β and C, 26,15 and 25 farms, respectively), based on net energy offered during maintenance (100%, 122% and 154% of requirements, respectively), showed that there was considerable area for improvement; the use of large quantities of concentrates is unjustified. Location, considerable on-farm feed production and zero grazing were associated with farm classification in group C. Rations used during the pre-breeding and the breeding periods offered 40-50% more net energy than required. Protein requirements were greatly exceeded (200-250%); alfalfa hay was the basic roughage and soybean and other oilseed meals (10% and 5%, respectively) were included in the concentrates. Calcium requirements were greatly exceeded as well. However, 1 out of 4 farms was providing inadequate amounts of phosphorus during maintenance. Moreover, adequate amounts of vitamins and trace minerals were offered by 37.9% of farms only, during maintenance. This situation was improved during the pre-breeding and the reeding periods (54.5% and 74.2%, respectively), but it was still far from desirable. It was estimated that balanced rations would decrease annual ram feeding expenses by at least 20€. At the same time, incidences of elevated body condition scores and their detrimental effects on ram fertility and some diseases, like urolithiasis, would be greatly reduced.